Detection of HIV-1-specific T-cell immune responses in highly HIV-exposed uninfected individuals by in-vitro dendritic cell co-culture. (17th July 2015) - Guardo, Alberto C.; Ruiz-Riol, Marta; Fernández, Emma; Maleno, Maria J.; Bargalló, Manel E.; León, Agathe; Climent, Nuria; García, Felipe; Gatell, Jose M.; Brander, Christian; Plana, Montserrat
Abstract : Background: Although virus-specific responses are rarely detected by conventional approaches, we report here the detection of T-cell responses in HIV-exposed seronegative (HESN) patients by two distinct assays. Methods: HIV-specific T-cell responses were analyzed by enzyme-linked immunospot in peripheral blood mononuclear cells from HESN patients after a 48-h co-culture with boosted dendritic cells. Additionally, a boosted flow cytometry approach was used to capture antiviral T-cell responses. Host genetic factors and T-cell activation were also analyzed to assess their implication on HIV exposure. Results: Of the 45 HESN individuals tested, up to 11 (24.4%) showed at least one response to peptide pools covering HIV Gag and Nef. A positive correlation was observed between the intensity ( P  = 0.0022) and magnitude ( P  = 0.0174) of the response detected in the HESN, and the viral load of the HIV-positive partner. Moreover, the result from the boosted flow and cytomix analyses showed a dominant Th1-like response pattern against HIV antigens, especially in CD8 + T-cell populations. Conclusions: The combined use of our boosted dendritic cell technique with a boosted flow cytometric approach allows us both to detect specific HIV-positive responses in a higher percentage of HESN patients and to define specific effector function profiles. This study contributes to a better understanding of resistance to HIV infection. Abstract : Supplemental Digital Content is available in the text